Pengaruh Faktor Makroekonomi Terhadap Dana Pihak Ketiga dan Market Share pada Bank Umum Syariah di Indonesia Tahun 2020-2024 - Ikha Fasikha; Meilana Widyaningsih (Jurnal BAABU AL-ILMI: Ekonomi dan Perbankan Syariah, 2026)
This research investigates the impact of broad economic factors, specifically inflation, interest rates, and currency exchange rates, on Third Party Funds (DPK) and the market presence of Islamic commercial banks in Indonesia from 2020 to 2024. Even though Islamic banks do not operate on an interest-based model, macroeconomic variables such as inflationary trends, primary interest rates, and fluctuations in exchange rates can still influence customer savings behavior and the ability of Islamic banks to grow their market share. This study utilizes a quantitative methodology involving multiple linear regression analysis. The secondary data used in this analysis were sourced from official reports provided by Bank Indonesia, the Financial Services Authority, and Statistics Indonesia. The research results reveal that inflation does not have a noticeable effect on Third Party Funds; however, interest rates and exchange rates significantly impact these funds. On the other hand, inflation plays a key role in market share dynamics, while interest rates and exchange rates show no significant effect on the market share of Islamic commercial banks. These findings offer crucial insights for regulators and professionals in the Islamic banking sector to formulate strategies aimed at enhancing fund mobilization and ensuring the stability of fund accumulation, especially amidst economic fluctuations. In addition, Islamic banks should be urged to create more adaptable funding strategies to respond effectively to global economic changes.